Seeing the whole picture: visualising socio-spatial power through augmented reality. Issue 2 (3rd July 2019) - Katell, Michael; Dechesne, Francien; Koops, Bert-Jaap; Meessen, Paulus
ABSTRACT: Augmented Reality (AR) will have important effects on the ways in which spaces and places take meaning for both users and non-users of AR. As the market penetration of AR increases, new claims will be made on certain spaces, superimposing AR contexts on the meanings and functions traditionally associated with these spaces, not only by AR users but also by AR designers and service providers, raising important and complex questions about regulatory approaches to mitigating information and power asymmetries. A regulatory strategy that promotes civil society and individual privacy requires that we thoroughly consider the implications of AR on the construction of public and private space. We employ a mix of real and fictional AR scenarios to interrogate the potential effects of AR use and design on the construction of spatial meaning, the orientation of social relations, and distributions of social power, and we make initial recommendations for regulation to address AR's possible negative effects.